REASONS BEHIND SUCCESS AND FAILURE OF BIOGAS TECHNOLOGY: A CASE OF DISTRICT DERA ISMAIL KHAN (PAKISTAN) - Syed Muhammad AMIR; Liu YONGGONG (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Since the beginning of the new century there is a trend in Bulgaria towards increasing demand for specialized tourism services. Although our country has unique combinations of natural and anthropogenic resources, they get quickly exhausted as an attraction. This requires continuous updating of tourism product in order to adapt it to the ever changing needs of users. Good prerequisites for that are presented in creating an integrated tourism product based on the available resources for development of rural and spa tourism in the region of the municipality of Velingrad - which is the subject of this research. On the one hand, the area is well-established and rich in mineral waters; it has the relevant facilities for development of SPA services and, on the other hand, it has the necessary prerequisites for development of rural tourism. The author states that, given the upcoming tourism regionalisation of the country, the creation of an integrated tourism product is the basis for achieving high competitiveness of tourism at international level.